Oil Price Pass-Through Into Consumer and Producer Prices With Monetary Policy in China: Are There Non-linear and Mediating Effects - Chen, Shuanglian; Ouyang, Shengyin; Dong, Hao (Frontiers in Energy Research, 2020)
Balancing the oil pass-through to consumer and producer prices is crucial for policymakers. This study aimed to advance associated thinking by examining how consumer and producer prices in China related to changes in global oil prices from 2006 to 2018. First we investigated the pass-through of oil spot prices to consumer prices as indicated by the consumer price index (CPI) and means of consumption price index (MCPI), and to producer prices as indicated by the producer price index (PPI) and means of production price index (MPPI), with a monetary policy in China. Furthermore, this study explored the non-linear and mediating effects of financial markets and government debt on linkages between oil prices and consumer/producer prices based on non-linear framework and causal steps approach, respectively. Our findings indicated some key points; for example, the pass-through of oil prices with a monetary policy in China shed light on a benchmark role in global oil markets. Additionally, the non-linear effect of oil prices on consumer/producer prices varied across the Brent and West Texas Intermediate (WTI) crude oil markets. Additionally, the mediating effect of government debt reflected the effectiveness in balancing the relationship between oil prices and producer prices. Government debt explained the -0.091 transition between the Brent oil price and the PPI and could explain the -0.095 transition between the Brent oil price and the MPPI, whereas for the transition due to financial markets were -0.064 and -0.080, respectively. These outcomes have important implications for stabilizing price levels in countries.